2006
DOI: 10.1016/j.idairyj.2005.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dairy farm and milk refrigeration on microbiological and microstructural characteristics of matured Serra da Estrela cheese

Abstract: This work was aimed at enumerating the viable microorganisms in ripened Serra da Estrela cheeses, manufactured from both refrigerated and non-refrigerated milk, in various dairies located throughout the demarcated region. Scanning electron microscopy was used to analyze the microstructure, and thus aid in understanding possible differences in their microbiological profile. The cheeses were allowed to ripen under controlled conditions, and sampled at 60, 90, 120, 150 and 180 d following manufacture. Viable numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…1c exemplifies the possibility of the simultaneous quantification of isobaric compounds, even at very different concentrations, as is the case for ethanol and formic acid (both at nominal mass of 47 Th) and demonstrates also the possibility to account for a contribution of an instrumental background at m/z = 47.024. Methanol is also detected at nominal mass 33 and the TOF allows the separation of the contribution of isobaric 18 …”
Section: Ptr-tof-ms Spectra Of Cheese Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…1c exemplifies the possibility of the simultaneous quantification of isobaric compounds, even at very different concentrations, as is the case for ethanol and formic acid (both at nominal mass of 47 Th) and demonstrates also the possibility to account for a contribution of an instrumental background at m/z = 47.024. Methanol is also detected at nominal mass 33 and the TOF allows the separation of the contribution of isobaric 18 …”
Section: Ptr-tof-ms Spectra Of Cheese Samplesmentioning
confidence: 99%
“…[14] Trentigrana is produced from partly skimmed raw cow's milk acidified with a mixture of Lactobacillus and coagulated by the addition of bovine rennet but, having a more restrictive protocol as compared with Grana cheese, the use of lysozyme and silage for the cow's feeding are not allowed. [15] At the 18 cheese factories belonging to the Trentingrana consortium, the milk used comes from a double milk collection: the full fat milk of the evening milking is delivered to the cheese factory in churns (traditional method) or in tanks at controlled temperature (18 • C) and undergoes a natural creaming process (or gravity separation [16] ) in large vats. After skimming the evening milk is added to the milk of the morning milking and used to produce cheese according to the standard cheese-making procedure of the Trentigrana.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is only manufactured with raw ewe's milk, salt and milk thistle flower for coagulation, and it is preferentially consumed as a soft cheese, with an average maturation of 1 month, although some consumers prefer to consume it as a hard cheese after at least 6 months of storage. Despite some published studies on the ''Serra da Estrela" cheese, that focus mainly on the microbial flora in the cheese, as well as the changes in some nutrients during ripening (Dahl, Tavaria, & Malcata, 2000;Macedo, Tavares, & Malcata, 2004;Partidário, Barbosa, & Boas, 1998;Tavaria, Franco, Carballo, & Malcata, 2003;Tavaria, Reis, & Malcata, 2006), the present work evaluates the effects of natural additives (chestnut flowers, lemon balm dry material and their decoctions) on the nutritional properties of cheese during its maturation.…”
Section: Introductionmentioning
confidence: 99%
“…Dahl, Tavaria, and Malcata (2000) reported that cheeses produced from refrigerated and non-refrigerated raw sheep milk present differences in microbiological profiles during ageing and in volatile patterns at the end of six months of ripening. The same research group (Tavaria, Reis, & Malcata, 2006) reported that cheeses manufactured with refrigerated milk were different in their micro-structural characteristics. Even if chemical composition, rheological behaviour and sensory attributes were closely associated with cheese micro-structure, the effect of cold-induced changes in cheeses on the perceptible sensory quality is still undemonstrated.…”
Section: Introductionmentioning
confidence: 99%